Theoretical approaches to risk management of investments in precious metals in the financial market - Pozniak, Roman (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article reveals the essence of risk from the perspective of several approaches – normative and descriptive – and provides an analysis of the types of risks associated with investing in precious metals on the financial market. It examines the ways in which investment risks in metals can be measured and how their impact can be mitigated through the application of various risk management strategies. Currently, companies are increasingly interested in expanding their investment activities in the financial market. This trend has been partially driven by the global financial crisis, the consequences of which affected virtually all economic actors. Companies have realized the necessity of determining the directions for investing their temporarily free cash assets, in order to protect themselves, to some extent, from crisis phenomena and not only preserve their financial resources but also to increase them. Investments in precious metals represent one of the oldest forms of capital preservation, which remain relevant to this day. Gold, silver, platinum, and palladium have traditionally functioned as “safe haven assets,” utilized to preserve value during periods of economic instability. The primary objective of such investments is to protect capital from inflation, devaluation, and other financial risks. Under conditions of increasing market uncertainty, precious metals continue to maintain their popularity among investors. As a result of this study, it can be concluded that any company’s investment activity is exposed to risk. Investments in precious metals are no exception, even though they are among the most reliable forms of investment. When engaging in investment activities in the precious metals market, companies must use both strategic and expert risk measurement approaches. For effective risk management in precious metals investment, it is advisable to apply strategies of diversification and hedging, which will help minimize potential losses to the fullest extent. A comprehensive approach to investment risk management – encompassing risk assessment through various methods and the use of diverse mitigation strategies – will enable investors to achieve the highest possible returns and increase their capital.

У статті розкривається сутність ризику з точки зору кількох підходів – нормативного та описового – та наведено аналіз видів ризиків, пов'язаних з інвестуванням у дорогоцінні метали на фінансовому ринку. Розглянуто способи вимірювання інвестиційних ризиків у метали та пом'якшення їхнього впливу шляхом застосування різних стратегій управління ризиками. Наразі компанії все більше зацікавлені в розширенні своєї інвестиційної діяльності на фінансовому ринку. Ця тенденція частково зумовлена світовою фінансовою кризою, наслідки якої торкнулися практично всіх економічних суб'єктів. Компанії усвідомили необхідність визначення напрямків інвестування своїх тимчасово вільних грошових активів, щоб певною мірою захистити себе від кризових явищ та не лише зберегти свої фінансові ресурси, а й примножити їх. Інвестиції в дорогоцінні метали є однією з найдавніших форм збереження капіталу, яка залишається актуальною й донині. Золото, срібло, платина та паладій традиційно функціонували як "безпечні активи", що використовуються для збереження вартості в періоди економічної нестабільності. Основною метою таких інвестицій є захист капіталу від інфляції, девальвації та інших фінансових ризиків. В умовах зростаючої ринкової невизначеності дорогоцінні метали продовжують зберігати свою популярність серед інвесторів. В результаті цього дослідження можна зробити висновок, що інвестиційна діяльність будь-якої компанії піддається ризику. Інвестиції в дорогоцінні метали не є винятком, хоча вони є одними з найнадійніших форм інвестування. Здійснюючи інвестиційну діяльність на ринку дорогоцінних металів, компанії повинні використовувати як стратегічні, так і експертні підходи до вимірювання ризиків. Для ефективного управління ризиками в інвестуванні в дорогоцінні метали доцільно застосовувати стратегії диверсифікації та хеджування, що допоможе максимально мінімізувати потенційні збитки. Комплексний підхід до управління інвестиційними ризиками, що охоплює оцінку ризиків за допомогою різних методів та використання різноманітних стратегій пом'якшення, дозволить інвесторам досягти максимально можливої прибутковості та збільшити свій капітал.
Теоретичні підходи до управління ризиками інвестування в дорогоцінні метали на фінансовому ринку
Keywords: financial market; investment activity; precious metals; risk management; descriptive approach; normative approach; diversification; hedging; фінансовий ринок; інвестиційна діяльність; дорогоцінні метали; управління ризиками; дескриптивний підхід; нормативний підхід; диверсифікація; хеджування